Outcomes of an Integrated Urology-Palliative Care Clinic for Patients With Advanced Urological Cancers: Maintenance of Quality of Life and Satisfaction and High Rate of Hospice Utilization Through End of Life. (September 2019) - Huen, Kathy; Huang, Cher; Liu, Hui; Kwan, Lorna; Pannell, Stephanie; Laviana, Aaron; Saucedo, Josemanuel; Lorenz, Karl; Bennett, Carol; Bergman, Jonathan
Introduction: Systematic integration of palliative care in a surgical setting is important, but has yet to be achieved. Despite evidence of early palliative care improving patients' quality of life, hospice utilization remains low. Through an integrated palliative care-urology clinic, we aim to assess the effect of early outpatient palliative care on hospice utilization, health-related quality of life (HRQOL) and satisfaction in patients with advanced urological cancers. Methods: Participants were recruited from 2012 through 2016 in the Greater Los Angeles Veterans Affairs Hospital. We partnered with palliative care clinicians to develop an integrated urology-palliative care clinic, where participants were seen by the palliative care team on the same day as their urological visit. The 12-item Short-Form Survey, Patient Satisfaction Questionnaire Short-Form, Patient Health Questionnaire, and Brief Pain Inventory were administered at initial and subsequent visits. Follow-up questionnaire results were compared between baseline and the 2 follow-up visits, and hospice utilization rates were assessed. Results: Fifty-three participants completed baseline questionnaires. Of those 22 (42%) patients completed at least one follow-up assessment. The median time for the first and second follow-up visits was 2.9 and 7.8 months, respectively. There were no significant differences in HRQOL and satisfaction between baseline and subsequent follow-up visits. A total of 36 (68%) of 53 participants who were enrolled at the start of the study were deceased. Of those, 29 (81%) expired within a home or inpatient hospice. Conclusions: Rates of hospice use were high in an integrated palliative care-urology model. Health-related quality of life and satisfaction did not worsen over time.